2014
DOI: 10.1080/15222055.2014.893470
|View full text |Cite
|
Sign up to set email alerts
|

More Judicious Use of Fish Oil in Cobia Feeds: II. Effects of Graded Fish Oil Sparing and Finishing

Abstract: Replacement of long‐chain (LC) polyunsaturated fatty acid (PUFA)‐rich fish oil with alternative lipids in aquafeeds typically reduces the LC‐PUFA content and associated nutritional value of farmed fish even if production performance is unaffected. Finishing can be used to augment tissue LC‐PUFA levels prior to harvest; however, the effectiveness of this strategy for use with the Cobia Rachycentron canadum is relatively unknown. For 8 weeks, Cobias (initial weight [mean ± SE] = 59.8 ± 0.2 g) were fed diets in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 52 publications
1
10
0
Order By: Relevance
“…Although an equivalent evaluation was not conducted in cobia, using partially or fully hydrogenated soybean oil instead of traditional soybean oil as the base lipid in DHA-supplemented feeds resulted in substantially greater tissue LC-PUFA levels [35], suggesting that it may have been unnecessary to supplement the hydrogenated soybean oil feeds to satisfy the DHA requirement of cobia. Greater fillet DHA enrichment was also observed among cobia fed blends of fish oil and SFA/MUFA-rich plant and animal-origin lipids instead of blends of fish oil and C 18 PUFA-rich soybean oil [39,40]. Following an identical experimental design to that employed herein (i.e., involving beef tallow-based feeds amended with EPA and/or DHA), it was demonstrated that reported n-3 LC-PUFA requirements of hybrid striped bass appear similarly overestimated in the context of abundant dietary SFA or MUFA [41].…”
Section: Discussionmentioning
confidence: 95%
“…Although an equivalent evaluation was not conducted in cobia, using partially or fully hydrogenated soybean oil instead of traditional soybean oil as the base lipid in DHA-supplemented feeds resulted in substantially greater tissue LC-PUFA levels [35], suggesting that it may have been unnecessary to supplement the hydrogenated soybean oil feeds to satisfy the DHA requirement of cobia. Greater fillet DHA enrichment was also observed among cobia fed blends of fish oil and SFA/MUFA-rich plant and animal-origin lipids instead of blends of fish oil and C 18 PUFA-rich soybean oil [39,40]. Following an identical experimental design to that employed herein (i.e., involving beef tallow-based feeds amended with EPA and/or DHA), it was demonstrated that reported n-3 LC-PUFA requirements of hybrid striped bass appear similarly overestimated in the context of abundant dietary SFA or MUFA [41].…”
Section: Discussionmentioning
confidence: 95%
“…Rather, it is more likely that the digestibility of the 100 SFA SOY feed was somewhat reduced compared with the other feeds. Although our previous research with SFA-rich lipids has not suggested digestibility is a major limiting factor (Trushenski et al 2011a(Trushenski et al , 2011cLaporte and Trushenski 2011;Crouse et al 2013;Trushenski and Kanczuzewski 2013;Trushenski et al 2013b;Woitel et al 2014aWoitel et al , 2014b, fish may not utilize SFAs as well as other fatty acids (Hua and Bureau 2009) and growth performance may be constrained by long-term feeding with diets containing predominantly SFAs (Trushenski and Bergman 2014). It is possible that blending SFA-rich lipids with ingredients containing some level of unsaturated fatty acids may be a means of addressing digestibility limitations while still mitigating the effects of fish oil sparing on tissue composition.…”
Section: Discussionmentioning
confidence: 97%
“…It is well established that feeds reduced in or free of fish oil are typically well accepted and utilized, so long as essential fatty acid requirements are met; it is equally well established that these dietary manipulations affect the fatty acid composition of the resulting fillets, causing them to contain lower levels of beneficial LCPUFAs (Glencross and Turchini 2011;Trushenski and Bowzer 2012;Pérez-Sánchez et al 2013). Alternative lipids containing reduced levels of C 18 polyunsaturated fatty acids (C 18 PUFAs) may not affect the composition of fish tissues to the extent that C 18 PUFA-rich lipids do (Laporte and Trushenski 2011;Trushenski et al 2011aTrushenski et al , 2011bTrushenski et al , 2011cTrushenski et al , 2011dTrushenski et al , 2013aTrushenski et al , 2013bTurchini et al 2011;Ramezani-Fard et al 2012;Trushenski and Kanczuzewski 2013;Woitel et al 2014aWoitel et al , 2014bTrushenski and Bergman 2014). Of the various lipids with potential "omega-3 sparing effect[s]" , saturated fatty acid (SFA)-rich lipids appear to be the most successful in terms of preserving tissue composition (Trushenski et al 2008(Trushenski et al , 2011aTrushenski and Kanczuzewski 2013;Woitel et al 2014a); however, SFA-rich lipids may not be well digested by all taxa or under all circumstances (Hua and Bureau 2009;Kanczuzewski and Trushenski 2015;Trushenski and Bergman FATTY ACIDS IN HYBRID STRIPED BASS FEEDS 161 2014).…”
mentioning
confidence: 99%
“…However, this finding may be most relevant in the context of finishing feeds used to tailor fillet fatty acid profile prior to harvest (Turchini et al., ; Trushenski & Bowzer, ; Woitel et al., ; Woitel et al. ).…”
Section: Discussionmentioning
confidence: 99%